2010
DOI: 10.4314/ijhr.v1i1.55345
|View full text |Cite
|
Sign up to set email alerts
|

Hiv/aids – related knowledge and sexual behaviour among secondary school students in Benin city

Abstract: a peer-reviewed online international journal allowing free unlimited access to abstract and full-text of published articles. The journal is devoted to the promotion of health sciences and related disciplines (including medicine, pharmacy, nursing, biotechnology, cell and molecular biology, and related engineering fields). It seeks particularly (but not exclusively) to encourage multidisciplinary research and collaboration among scientists, the industry and the healthcare professionals. It will also provide an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Other misconceptions recorded included: HIV/AIDS infected person can be fully cured, can never survive, healthy looking person can not have HIV/AIDS and cannot also infect others with the AIDS virus. Previous studies also recorded these misconceptions (Peltzer and Promtussananon, 2005;Unigbe and Ogbeide, 2005;Ojieabu et al, 2008). UNAIDS (2003) noted that general awareness of AIDS is no longer important in AIDS prevention but accurate knowledge of how HIV is transmitted.…”
Section: Discussionmentioning
confidence: 99%
“…Other misconceptions recorded included: HIV/AIDS infected person can be fully cured, can never survive, healthy looking person can not have HIV/AIDS and cannot also infect others with the AIDS virus. Previous studies also recorded these misconceptions (Peltzer and Promtussananon, 2005;Unigbe and Ogbeide, 2005;Ojieabu et al, 2008). UNAIDS (2003) noted that general awareness of AIDS is no longer important in AIDS prevention but accurate knowledge of how HIV is transmitted.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, the prevalence has stabilized (UN-AIDS, 2008). Some suggest this may be due to the enormous inflow of funds from the Nigerian government and nongovernmental organizations including the American President's Emergency Plan for AIDS Relief (see Ojieabu, Erah, & Okafor, 2008). Declines in prevalence have also been partly attributed to the launching of a national health policy in 2000 of which the main target was to change behaviors that led to the contraction of STIs among adolescents (Slap et al 2003).…”
Section: Contextmentioning
confidence: 96%
“…It is one of the poorest and least industrialized states, yet it has one of the highest literacy rates (Policy Project, 2004). Several studies point to the higher percentages of sexually active youth in this state compared with most other states in the country, an active commercial sex industry, and international sex trafficking as indicators that youth in the state are vulnerable to STIs and HIV (Ojieabu et al, 2008;Policy Project, 2004;Temin et al, 1999;Women's Health and Action Research Center [WHARC], 2003). Youth vulnerability was confirmed in a recent report published by the WHARC that noted increases in HIV prevalence from 7% in 1995 to 13.3% in 2000 with approximately 74.6% of these infections among adolescent girls (WHARC, 2003).…”
Section: Contextmentioning
confidence: 97%
“…Similarly, a study among secondary school students in Benin City by Ojieabu et al reported that awareness of HIV/AIDS was high; although there were misconceptions about the causes, and transmission was high (91.4% and 93.1%) respectively among respondents [8] knowledge on prevention was poor as only 40% of the respondents knew how to avoid contracting HIV/AIDS. The study concluded that despite the various educational efforts to address the problems of HIV/AIDS, the knowledge about it by secondary school students in Benin City is still poor and the adolescents still engage in risky behaviour.…”
Section: Introductionmentioning
confidence: 95%
“…[6] Late adolescence (15-19 years) is very important as sexual debut and experimentation usually occurs during this period. [8] A study in Tanzania reported that all the students investigated have high knowledge on the issues surrounding HIV/AIDS. [9] Moreover, the students are of the opinion that schools could further promote AIDS education as they all agreed that awareness and knowledge lead to decline in the engagement in risky behaviour.…”
Section: Introductionmentioning
confidence: 99%